2004
DOI: 10.1037/0096-1523.30.1.79
|View full text |Cite
|
Sign up to set email alerts
|

What Kind of Memory Supports Visual Marking?

Abstract: In visual search tasks, if a set of items is presented for 1 s before another set of new items (containing the target) is added, search can be restricted to the new set. The process that eliminates old items from search is visual marking. This study investigates the kind of memory that distinguishes the old items from the new items during search. Using an accuracy paradigm in which perfect marking results in 100% accuracy and lack of marking results in near chance performance, the authors show that search can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 47 publications
1
41
0
Order By: Relevance
“…In the Gap condition, the maintenance of inhibition in the face of irrelevant capture supports the assertion that that VWM can bias selection towards previously unattended locations during search (Al-Aidroos et al, 2012;Emrich et al, 2008;McCarley et al, 2003). In addition, our data indicate the contribution of memory-based inhibition to the preview benefit is sensitive to both the number and salience of objects that elicit capture during search (Jiang & Wang, 2004;Watson & Humphreys, 1997;Yantis & Johnson, 1990;Yantis & Jones, 1991). This dependency suggests efficient search relies on the effective integration of separate forms of guidance rather than a single unitary resource.…”
Section: Jiang and Wang (2004) Interpreted A Similar Dependency As Evsupporting
confidence: 79%
See 1 more Smart Citation
“…In the Gap condition, the maintenance of inhibition in the face of irrelevant capture supports the assertion that that VWM can bias selection towards previously unattended locations during search (Al-Aidroos et al, 2012;Emrich et al, 2008;McCarley et al, 2003). In addition, our data indicate the contribution of memory-based inhibition to the preview benefit is sensitive to both the number and salience of objects that elicit capture during search (Jiang & Wang, 2004;Watson & Humphreys, 1997;Yantis & Johnson, 1990;Yantis & Jones, 1991). This dependency suggests efficient search relies on the effective integration of separate forms of guidance rather than a single unitary resource.…”
Section: Jiang and Wang (2004) Interpreted A Similar Dependency As Evsupporting
confidence: 79%
“…Extending the current design to include larger set sizes, however, may distinguish the robust inhibition observed in this study from the more fragile inhibition thought to operate in larger displays (Al-Aidroos et al, 2012;Jiang & Wang, 2004).…”
Section: Jiang and Wang (2004) Interpreted A Similar Dependency As Evmentioning
confidence: 97%
“…Interestingly, this capacity limit corresponds to the capacity of visual short-term memory (Cowan, 2001;Luck & Vogel, 1997). In fact, previous studies have found that the preview benefit is greatest when the number of previewed items is within this capacity (Jiang, Chun, & Marks, 2002), providing evidence that this effect may depend in part on this sort of memory store (but see Jiang & Wang, 2004). Regardless of whether this effect is dependent on memory processes, the findings that the preview effect is affected by the number of previewed items and by ased away from old items confirms the findings of Watson and Inglis (2007), we have demonstrated that this effect does not persist throughout the entire search process.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recently, Jiang and Wang (2004) also found evidence for transience in prioritized selection and concluded that the memory trace for asynchrony rapidly decays allowing prioritized selection to occur only during a limited period of time. They did not vary the interval between the presentation of the new elements and the presentation of the target.…”
mentioning
confidence: 99%